Probucol-induced hERG Channel Reduction can be Rescued by Matrine and Oxymatrine in vitro - Shi, Yuan-Qi; Fan, Pan; Zhang, Guo-Cui; Zhang, Yu-Hao; Li, Ming-Zhu; Wang, Fang; Li, Bao-Xin (Current Pharmaceutical Design, 2019)
Background: The human ether-a-go-go-related gene (hERG) potassium channel is the rapidly activating component of cardiac delayed rectifier potassium current (IKr), which is a crucial determinant of cardiac repolarization. The reduction of hERG current is commonly believed to cause Long QT Syndrome (LQTs). Probucol, a cholesterol-lowering drug, induces LQTs by inhibiting the expression of the hERG channel. Unfortunately, there is currently no effective therapeutic method to rescue probucol-induced LQTs. Methods: Patch-clamp recording techniques were used to detect the action potential duration (APD) and current of hERG. Western blot was performed to measure the expression levels of proteins. Results: In this study, we demonstrated that 1 μM matrine and oxymatrine could rescue the hERG current and hERG surface expression inhibited by probucol. In addition, matrine and oxymatrine significantly shortened the prolonged action potential duration induced by probucol in neonatal cardiac myocytes. We proposed a novel mechanism underlying the probucol induced decrease in the expression of transcription factor Specificity protein 1 (Sp1), which is an established transactivator of the hERG gene. We also demonstrated that matrine and oxymatrine were able to upregulate Sp1 expression which may be one of the possible mechanisms by which matrine and oxymatrine rescued probucol-induced hERG channel deficiency. Conclusion: Our current results demonstrate that matrine and oxymatrine could rescue probucol-induced hERG deficiency in vitro, which may lead to potentially effective therapeutic drugs for treating acquired LQT2 by probucol in the future.
Keywords: cardiac repolarization